1977
DOI: 10.1136/jnnp.40.11.1060
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase activity and menstrual remissions in myasthenia gravis.

Abstract: SUMMARY Menstrually related temporary remissions of myasthenic symptoms are reported to occur in 25 to 50% of female patients. Even though this has been attributed to hormonal changes associated with the menstrual cycle the underlying mechanism of this hormonal influence has remained elusive. The present study demonstrated a cyclical variation in the activity of red cell acetylcholinesterase (EC 3.1.1.7) enzyme (AChE) with a marked reduction at the time of menstrual remission of symptoms of myasthenia. These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…[74][75][76] In contrast to these disorders, myasthenia gravis generally improves premenstrually. 77 Although one early report indicated better outcomes if breast surgery was performed in the luteal phase, 78 subsequent investigators have been unable to confirm this finding. 79…”
Section: I S C E L L a N E O U S D I S O R D E R Smentioning
confidence: 99%
“…[74][75][76] In contrast to these disorders, myasthenia gravis generally improves premenstrually. 77 Although one early report indicated better outcomes if breast surgery was performed in the luteal phase, 78 subsequent investigators have been unable to confirm this finding. 79…”
Section: I S C E L L a N E O U S D I S O R D E R Smentioning
confidence: 99%
“…Most patients in this subgroup present the human leukocyte antigen-B8 and -DR3 phenotype (30,31). Modulation of the clinical symptoms of MG during pregnancy or menstruation has been reported, and this phenomenon disappears after thymectomy (32).…”
mentioning
confidence: 98%
“…Current studies demonstrate no increase in spontaneous abortion rate (14,15). Some reports have shown a tendency for MG to improve before and during menstruation, whereas others have shown a worsening during this same time (16). A prospective study showed that MG frequently exacerbates before and during the menstrual period in 67% of patients (5).…”
Section: Discussionmentioning
confidence: 94%